If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 30 = 6(v + -7) + 6v Reorder the terms: 30 = 6(-7 + v) + 6v 30 = (-7 * 6 + v * 6) + 6v 30 = (-42 + 6v) + 6v Combine like terms: 6v + 6v = 12v 30 = -42 + 12v Solving 30 = -42 + 12v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-12v' to each side of the equation. 30 + -12v = -42 + 12v + -12v Combine like terms: 12v + -12v = 0 30 + -12v = -42 + 0 30 + -12v = -42 Add '-30' to each side of the equation. 30 + -30 + -12v = -42 + -30 Combine like terms: 30 + -30 = 0 0 + -12v = -42 + -30 -12v = -42 + -30 Combine like terms: -42 + -30 = -72 -12v = -72 Divide each side by '-12'. v = 6 Simplifying v = 6
| 3.1x+5=8 | | 5x-8y-40=0 | | 5x-8y-4=0 | | (28*x)+6=1 | | 0=y^2+y-12 | | -6x=-9.6 | | -5m=6m-1 | | 0=4m^2-20m | | -6x=-9.1 | | -1/4=-2/3u-1/5 | | 0=p^2-5p | | 0=y^2-10y+9 | | y=-(8)+3 | | 8+y-14=2 | | y=-(3)+3 | | 294=6s^2 | | 9a-a-5a= | | 9/x-1(7/x-3) | | (x)1.5+(y)0.5=18 | | 1/2+(t+7)=32 | | -5(3)(-5)(4)= | | (4-w)(2w+5)=0 | | 3x-(6)=30 | | 4x-3+6x+23=180 | | (4u-7)(8-u)=0 | | 30x+50y+70z=600 | | y=9/2x+5 | | 2x+3+25=45 | | 3(-4)-6/-4=12 | | 3j+(4/3)=3j | | -(-5v+y)-(-6y+v)= | | (-10y^2-14)-(-5y^2+7)=0 |